Mahaguru RSI Agastya roles in the Indonesian development of the dharma civilization - Marsono; Ni Wayan Sri Rahayu; Ni Komang Sutriyanti (Life and Death: Journal of Eschatology, 2023)
This research discusses Rsi Agastya, who is significant in Hindu civilization. Rsi Agastya's believed to be a priest who brought and taught Hindu teachings both in India and Indonesia. Because of this excellent service, various Dharma terms were given to Rsi Agastya, such as Agastya Yatra and Pita Segara. The narrative regarding the presence of Rsi Agastya in the archipelago is thought to take the form of a play that is then put together, combined with epics, namely stories from the Mahābhārata. The strong influence of Rsi Agastya's teachings can be seen through archaeological discoveries in statues and temples, such as the Clown Temple, specifically intended as a place to worship Rsi Agastya. From the archaeological findings, it can be seen that Rsi Agastya is not considered a Hindu priest but is positioned as Adi Guru and is even considered a representation of Shiva.